Pengaruh Leverage, Likuiditas Dan Pertumbuhan Penjualan Terhadap Kinerja Keuangan Perusahaan Sektor Teknologi Yang Terdaftar Di Bursa Efek Indonesia Periode 2019-2023 - Samsudin, Dimas Tegar Penggalih; Hanifah, Azimah (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Lamappapoleonro, 2025)
This study aims to determine and analyze the effect of leverage (CR), liquidity (DER), and sales growth on the financial performance (ROA) of companies in the technology sector. This study is a quantitative study of an associative nature. The population of this study consists of 46 technology companies listed on the Indonesia Stock Exchange (IDX) from 2019 to 2023. The sample was selected using purposive sampling, resulting in 12 companies. The data analysis technique used in this study is multiple linear regression analysis. The results of this study indicate that leverage (CR) has a positive but insignificant effect on the financial performance (ROA) of companies, liquidity (DER) has a negative and significant effect on the financial performance (ROA) of companies, and sales growth has a positive and significant effect on the financial performance (ROA) of companies. Simultaneously, leverage, liquidity, and sales growth have an effect on financial performance.